2018
DOI: 10.1111/pbi.13035
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SrUGT76G1 in Stevia alters major steviol glycosides composition towards improved quality

Abstract: Summary Steviol glycosides ( SG s) are extracted from Stevia leaves for use as a natural sweetener. Among SG s, stevioside is most abundant in leaf extracts followed by rebaudioside A (Reb A). However, Reb A is of particular interest because of its sweeter and more pleasant taste compared to stevioside. Therefore, the development of new Stevia varieties with a higher Reb A to stevioside ratio would be desirable for the production of higher quality natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…A skewing of the dulcoside A:Reb C ratio is also evident, though not as dramatic given that Reb C content is normally much greater than dulcoside A in control plants. The effects of 76G1-AY overexpression on the stevioside:Reb A, and dulcoside A:Reb C ratios in this study are very consistent with similar transgenic plant results recently reported 9 . These four SG compounds were the only ones analyzed in that study, however, due to limitations in their detection of the less abundant SG species.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A skewing of the dulcoside A:Reb C ratio is also evident, though not as dramatic given that Reb C content is normally much greater than dulcoside A in control plants. The effects of 76G1-AY overexpression on the stevioside:Reb A, and dulcoside A:Reb C ratios in this study are very consistent with similar transgenic plant results recently reported 9 . These four SG compounds were the only ones analyzed in that study, however, due to limitations in their detection of the less abundant SG species.…”
Section: Discussionsupporting
confidence: 93%
“…Subsequent induction of callus and the maintenance of callus under Hyg selection was also conducted in the dark until regeneration. Very recently, researchers reported using tissue cultured leaves as the explant and successfully obtained stable transgenic Stevia plants 9,26 ; this suggests that both types of originating explant are suitable for efficient transformation. Similar to our results, this same research group also concluded that a prolonged period of dark incubation was critical for obtaining high efficiency Stevia transformation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hydroxyl groups of steviol are glycosylated by the enzymes uridine diphosphate (UDP)-glycosyltransferases (UGTs), and the number of sugars attached by UGTs generates the various SGs ( Brandle & Telmer, 2007 ). The UGT74G1 enzyme is involved in the conversion of steviolbioside to stevioside, while the UGT76G1 enzyme converts stevioside into rebaudioside A ( Kim et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%